Optimalisasi Tata Kelola Berkelanjutan Destinasi Wisata Pantai Tete: Studi Kasus Area Pantai Militer - Sudarmi, Sudarmi; Rusdi, Muh. (Jurnal Master Pariwisata (JUMPA), 2022)
Sustainable Tourism Management has now become one of the main targets in environmental conservation. Including coastal tourism management through Ecotourism. The purpose of this study is to describe the evaluation of proper governance in optimizing the potential of Tete beach in Bone Regency of South Sulawesi to become a sustainable tourist destination. This study uses descriptive qualitative approach and uses observation, interviews, and documentation in collecting the data. The sampling technique used in this study was purposive sampling. The steps in analyzing the data are data processing, data analysis, and interpretation of results. The results show that the governance and the management of Tete Beach are not properly conceptualized. And so far, Tete beach management is still not optimal. These affect the local community income. Tete beach is commonly used as a military training are by TNI. Therefore it is necessary to have good planning in developing Tete beach to become a sustainable mainstay tourist destination. Eventually, good coordination is needed from the regional government, the TNI, the private sector, and the local community to increase the income of local community. Keywords: Optimization, Sustainable Coastal Management, Tete Beach.